Textile History and the Consumer Epidemic: An Anthropological Approach to Popular Consumption and the Mass Market - McCracken, Grant (Material Culture Review, 1990)
An issue central to the history oftextiles is how and with what consequences the cultural significance of textiles has changed. In this paper I will use an anthropological perspective to argue that the cultural or symbolic properties of textiles have played an important role in the transformation of western societies from the sixteenth century onwards. This argument will be made in three parts: first, that the western modernity was driven just as much by a "consumer revolution" as an industrial one; second, that the consumer revolution was driven by the effort to invest material culture and clothing with new cultural meanings; and finally, that this process of meaning investment was driven by changing definitions of social groups and the individual. The paper will summarize past research that bears on this question and suggest new avenues of research that issue from it. Résumé L’intérêt que présente l’histoire des textiles tient notamment à la façon dont a évolué la signification culturelle des textiles et à ses conséquences. L’auteur se propose de montrer ici, dans une perspective anthropologique, le rôle important que les propriétés culturelles ou symboliques des textiles ont joué dans la transformation des sociétés occidentales depuis le XVIe siècle. Trois étapes mèneront à cette conclusion. Nous verrons en premier lieu que la modernité occidentale a été le fait tout autant d’une révolution de la consommation que d’une révolution industrielle; deuxièmement, que cette révolution de la consommation s’est produite sous la poussée de l’effort visant à attribuer de nouvelles significations culturelles à la culture matérielle et à l’habillement; enfin, que le processus d’attribution de nouvelles significations découle de nouvelles définitions des groupes sociaux et de l’individu. L’article résume les recherches existantes sur la question et propose de nouvelles avenues de recherche à explorer pour y donner suite.